Solve for x:x/5 - 2 = x/2 + 3
Put each term in x/5 - 2 over the common denominator 5: x/5 - 2 = x/5 - (10)/5:x/5 - (10)/5 = x/2 + 3
x/5 - (10)/5 = (x - 10)/5:(x - 10)/5 = x/2 + 3
Put each term in x/2 + 3 over the common denominator 2: x/2 + 3 = x/2 + 6/2:(x - 10)/5 = x/2 + 6/2
x/2 + 6/2 = (x + 6)/2:(x - 10)/5 = (x + 6)/2
Multiply both sides by 10:(10 (x - 10))/5 = (10 (x + 6))/2
10/5 = (5×2)/5 = 2:2 (x - 10) = (10 (x + 6))/2
10/2 = (2×5)/2 = 5:2 (x - 10) = 5 (x + 6)
Expand out terms of the left hand side:2 x - 20 = 5 (x + 6)
Expand out terms of the right hand side:2 x - 20 = 5 x + 30
Subtract 5 x from both sides:(2 x - 5 x) - 20 = (5 x - 5 x) + 30
2 x - 5 x = -3 x:-3 x - 20 = (5 x - 5 x) + 30
5 x - 5 x = 0:-3 x - 20 = 30
Add 20 to both sides:(20 - 20) - 3 x = 20 + 30
20 - 20 = 0:-3 x = 30 + 20
30 + 20 = 50:-3 x = 50
Divide both sides of -3 x = 50 by -3:(-3 x)/(-3) = 50/(-3)
(-3)/(-3) = 1:x = 50/(-3)
Multiply numerator and denominator of 50/(-3) by -1:Answer: x = (-50)/3
Answer: x - 5/x + 1
Step-by-step explanation:
This algebraic fraction
The task to be performed here is factorisation and simplification. Now going by the question,
x² + 4x - 45/x² + 10x + 9, the factorisation of
x² + 4x - 45 = x² + 9x - 5x - 45
= x(x + 9 ) - 5(x + 9 )
= ( x + 9 )(x - 5 ), don't forget this is the algebraic fraction's Numerator
The second part
x² + 10x + 9 = x² + x + 9x + 9
= x(x + 1) + 9( x + 1 )
= ( x + 9 )( x + 1 ), this is the algebraic denominator.
Now place the second expression which is the denominator under the first expression which is the numerator.
( x + 9 )( x - 5 )/( x + 9 )( x + 1 ).
You can see that, ( x + 9 )/( x + 9 ) divide each other , therefore therr then cancelled and left with
x - 5/x + 1
Answer:
A
Step-by-step explanation:
ewqrui
Answer:
3 3/5 bags
Step-by-step explanation:
We have to find the surface area of the floor of the cage first.
The cage measures 1 yard wide by 6 feet long.
1 yard = 3 feet
The floor of the cage is rectangular, so, the surface area of the floor of the cage is therefore:
3 * 6 = 18 square feet
One bag of shavings covers 5 square feet.
To find the number of bags we need to cover the floor, we divide the surface area of the floor by the number of bags per square feet.
The number of bags needed for the floor of the cage is therefore :
18 / 5 = 3 3/5 bags
Answer:
![(AB)^T = B^T.A^T (Proved)](https://tex.z-dn.net/?f=%28AB%29%5ET%20%3D%20B%5ET.A%5ET%20%20%28Proved%29)
Step-by-step explanation:
Given (AB )^T= B^T. A^T;
To prove this expression, we need to apply multiplication law, power law and division law of indices respectively, as shown below.
![(AB)^T = B^T.A^T\\\\Start, from \ Right \ hand \ side\\\\B^T.A^T = \frac{B^T.A^T}{A^T}.\frac{B^T.A^T}{B^T} (multiply \ through) \\\\ = \frac{A^{2T}.B^{2T}}{A^T.B^T} \\\\=\frac{(AB)^{2T}}{(AB)^T} \ \ (factor \ out \ the power)\\\\= (AB)^{2T-T} \ (apply \ division \ law \ of \ indices; \ \frac{x^a}{x^b} = x^{a-b})\\\\= (AB)^T \ (Proved)](https://tex.z-dn.net/?f=%28AB%29%5ET%20%3D%20B%5ET.A%5ET%5C%5C%5C%5CStart%2C%20from%20%5C%20Right%20%5C%20hand%20%5C%20side%5C%5C%5C%5CB%5ET.A%5ET%20%3D%20%5Cfrac%7BB%5ET.A%5ET%7D%7BA%5ET%7D.%5Cfrac%7BB%5ET.A%5ET%7D%7BB%5ET%7D%20%28multiply%20%5C%20through%29%20%5C%5C%5C%5C%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%3D%20%5Cfrac%7BA%5E%7B2T%7D.B%5E%7B2T%7D%7D%7BA%5ET.B%5ET%7D%20%5C%5C%5C%5C%3D%5Cfrac%7B%28AB%29%5E%7B2T%7D%7D%7B%28AB%29%5ET%7D%20%5C%20%5C%20%28factor%20%5C%20out%20%5C%20the%20power%29%5C%5C%5C%5C%3D%20%28AB%29%5E%7B2T-T%7D%20%20%5C%20%28apply%20%5C%20division%20%5C%20law%20%5C%20of%20%5C%20indices%3B%20%5C%20%5Cfrac%7Bx%5Ea%7D%7Bx%5Eb%7D%20%3D%20x%5E%7Ba-b%7D%29%5C%5C%5C%5C%3D%20%28AB%29%5ET%20%5C%20%28Proved%29)